The EC and the Locational Choice of Swedish Multinational Companies - Birgitta Swedenborg (The Research Institute of Industrial Economics (IUI), 1990)
In a world with multinational companies (MNC's) changes such as those implied by the realization of EC's internal market will affect the locational choice made by geographically mobile MNC's outside the EC. The reason is that any change which affects the competitive advantage of EC producers relative to non-EC producers will alter the choice between MNC exports to and local production in the EC. This paper presents an empirical analysis of this issue. It uses comprehensive micro data on Swedish MNC production and trade for the period 1965-86 to test hypotheses regarding the effects of European trade policy on the locational choice of Swedish MNC's in that period. The results show that being part of a trade liberalization area strongly stimulates exporting relative to producing abroad by MNC's. It is suggested that this should be relevant to an evaluation of the effects of the EC internal market on non-EC members like Sweden.
Keywords: F13; F23; R30; 330; Multinational Firms; Geographical location; European trade policy